2014
DOI: 10.2174/1872312808666140317154110
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Characterization of Anti-cancer Agent Gefitinib in Human Hepatocytes

Abstract: Intensive Biotransformation studies on Gefitinib could play a significant role in designing and synthesizing new drugs around the core structure of Gefitinib. These studies may be useful in developing an entirely new drug by blocking the metabolic spots in Gefitinib. Gefitinib (Iressa) was the first oral epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor. Gefitinib shows toxicity to cancer cells and has the capability to inhibit the growth of cancer cells. Gefitinib is considered as one of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Studies indicated that atropaldehyde resulted in an accumulation of reactive species and toxicity by inhibiting the detoxifying enzymes glutathione S-transferase and aldehyde dehydrogenase [16]. The metabolism of GEF has been extensively investigated in vitro and in vivo [17][18][19][20]. Most of GEF was metabolized in liver and mainly excreted in feces, less than 7% in the urine, irrespective of dose route or species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicated that atropaldehyde resulted in an accumulation of reactive species and toxicity by inhibiting the detoxifying enzymes glutathione S-transferase and aldehyde dehydrogenase [16]. The metabolism of GEF has been extensively investigated in vitro and in vivo [17][18][19][20]. Most of GEF was metabolized in liver and mainly excreted in feces, less than 7% in the urine, irrespective of dose route or species.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the bioactivation of GEF are limited. To date, only glutathione-adducts were unraveled in microsomes and hepatocytes [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…The removal of the morpholine ring structure, as observed for the formation of metabolite M2, is well-established for mammalian biotransformation of related alkylmorpholine-structures [14, 15], although sometimes without the extensive oxidation of the remaining alkoxy-chain observed for copanlisib, leading to M2 and finally resulting in M4. However, apparently there are significant differences between species and between in vitro and in vivo findings regarding the extent of oxidative degradation of morpholine structures, as described, e.g., for gefitinib, which undergoes oxidation of the alkoxy side-chain only in vitro, while in vivo in man only oxidation products of the morpholine with ring opening are described [1618]. …”
Section: Discussionmentioning
confidence: 99%
“…Organ-on-a-chip [17] is an ongoing research to hasten the process of drug discovery and development. In vitro drug screening and safety testing [18][19][20] are essential to minimize extensive studies on laboratory animals. Microbioreactors designed as per the need of the study will be highly beneficial to understand the potency and toxicity of the developed drug molecules.…”
Section: Microbioreactors In Drug Discoverymentioning
confidence: 99%